```Question 232102
You got one right!!!  Good job.

Here is the problem worked for you:

I will solve 6M + N = 28 for "M"

6M + N = 28
6M = 28 - N
M = (28 - N)/6

Now that we have that answer for M, substitute it into the equation M - 7N = 62 to give us this equation:

(28 - N)/6 - 7N = 62

First thing we want to do now is get rid of our fraction!
We do that by multiplying each of the 3 terms by the denominator 6.  That will give us this equation:

28 - N - 42N = 372

Now we combine like terms:

28 - 43N = 372

Next, we subtract 28 from each side of the equation:

****don't forget that leaves us with a NEGATIVE 43N****

-43N = 344

Finally, we divide both sides by a -43 to get:

N=-8

Now that we have N's value, we plug that back into either original equation you want, I'll use 6M + N = 28

Plugging N's value in to that equation, we get:

6M + (-8) = 28

Subtract (-8) from both sides:

***subtacting a negative number turns it to a positive***

Now we have:

6M = 36

Divide each side by 6 to get:

M = 6